1905 Minn. Gen. Laws 162-63, An Act Amending General Statutes of 1894, § 6445, Relating to Manslaughter, ch. 125, § 1. - (:unkn) unknown (General Publisher, 1905)
By shooting another with a gun, or other firearm when resulting from carelessness in mistaking the person shot for a deer or other animal is manslaughter in the first degree
--
Keywords: COMMITTING CRIME W/ WEAPON